CULTURE-SPECIFIC PROPERTIES OF GREETING IN ACEHNESE AND TURKISH: A SOCIOLINGUISTIC STUDY IN CONVERSATIONAL OPENING - Risdadi, Sabar; Ramli, Ramli; Fitriani, Siti Sarah; Iskandar, Denni (Linguistik Indonesia, 2023)
Greeting is widely used in establishing social interactions. However, due to cultural backgrounds, history, and geographical location differences, greetings are very different. This paper aims to examine differences between Acehnese and Turkish greetings reflected from the form, type, and function.Â  Forty people involved in this study. Half of them are the fluent Acehnese speakers who live in Banda Aceh, Greater Aceh, and Sabang. The other half is Turkish people who live in the Turkic-speaking community in Aceh. The data were collected from direct observation and survey. The data were analyzed based on five steps, namely determining, classifying, analyzing, describing, and drawing the conclusion.Â  The results showed that while both countries use verbal/non-verbal greetings and formal /non-formal greetings, Acehnese greetings are limited. Furthermore, Acehnese used seasonal greetings only for Eid al-Fitr and Eid al-Adha whereas Turkish used it in various ways and divided into two categories: time-bound greetings and time-free greetings.